2014
DOI: 10.1007/s10393-014-0964-5
|View full text |Cite
|
Sign up to set email alerts
|

Need for Enhanced Environmental Representation in the Implementation of One Health

Abstract: Issues of global environmental change, global health, emerging disease, and sustainability present some of the most complex challenges of the twenty-first century. Individual disciplines cannot address these issues in isolation. Proactive, innovative, and trans-disciplinary solutions are required. Recognizing the inherent connectedness of humans, animals, plants, and their shared environment, One Health encourages the collaboration of many disciplines-including human and veterinary medicine, public health, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…This is not surprising as the OH initiative has been gaining momentum over the past decade, and the amount of interdisciplinary research has been shown to be increasing (Stärk et al 2015; Van Noorden 2015). Nonetheless, segregation between disciplines still persists, particularly between the veterinary and ecological sciences (Manlove et al 2016), and future interdisciplinary studies should ensure that the ecosystem component is properly represented (Barrett and Bouley 2015). Most identified studies described modeling approaches, either as mathematical modeling of infectious diseases or economic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as the OH initiative has been gaining momentum over the past decade, and the amount of interdisciplinary research has been shown to be increasing (Stärk et al 2015; Van Noorden 2015). Nonetheless, segregation between disciplines still persists, particularly between the veterinary and ecological sciences (Manlove et al 2016), and future interdisciplinary studies should ensure that the ecosystem component is properly represented (Barrett and Bouley 2015). Most identified studies described modeling approaches, either as mathematical modeling of infectious diseases or economic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We observed increased odds of B. tribocorum infection in rats associated with higher minimum temperatures and decreased odds of infection associated with low‐rise apartment buildings. This study analysed data across several levels of biological organization in an application of One Health problem solving (Barrett & Bouley, ; Estrada‐Peña et al., ). Future studies could apply similar techniques to other pathogens in rats, as well as urban and non‐urban wildlife species.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the pervasiveness of urban rats throughout the world and the potentially dangerous pathogens they carry, the influence of the microenvironment and weather on pathogen prevalence has not been well studied (Rothenburger et al., ). Furthermore, the exclusion of environmental characteristics in many studies of host‐pathogen systems has prompted some researchers to call for increased integration of environmental factors in the application of One Health problem solving (Barrett & Bouley, ). This is important because information about the kinds of environments and weather patterns that support infected rats could be used to develop targeted surveillance and interventions for both people and rats, which may also reduce the risk of rat‐associated zoonoses in people.…”
Section: Introductionmentioning
confidence: 99%
“…Also, previous studies show limited medical representation in One Health and infectious disease publications (49, 50). One Health mainly discusses collaborations between human and animal health issues at present but other disciplines, such as environmental and social sciences, should also be integrated (7, 5153). These partnerships currently only represent a minor share of the One Health research community.…”
Section: Discussionmentioning
confidence: 99%